Effect of Exchange Current Density on Current Distribution at Planar-Type SOFC Anodes. (30th May 2017) - Takino, Keisuke; Tachikawa, Yuya; Shiratori, Yusuke; Taniguchi, Shunsuke; Sasaki, Kazunari
Abstract : Cell stack structure of solid oxide fuel cells (SOFCs) affects to their performance. Its optimization is important to realize highly efficient SOFCs. In this study, we focus on the numerical simulation method combined with experimentally obtained exchange current density. Deriving the anode exchange current density for fully pre-reformed methane-fueled SOFCs, the effect on the current distribution is evaluated. Current distribution was calculated using variable anode exchange current density after taking into account the pressure of CO and CO2 .